Director's report of research in Kansas 2013 - Kansas State University. Agricultural Experiment Station (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2017)
This report contains the title, author, and publication information for manuscripts published by station scientists.
DRR13
Keywords: Kansas; Agricultural Experiment Station; Research; Publications; Finances; Projects